ANALISIS PERSEPSI KEMANFAATAN, PERSEPSI KEMUDAHAN, KEPERCAYAAN, GAYA HIDUP, LITERASI KEUANGAN, DAN RISIKO TERHADAP PENGGUNAAN QRIS SEBAGAI ALAT PEMBAYARAN DIGITAL PADA MAHASISWA DI YOGYAKARTA - Putri, Melisa Tania; Hatta, Atika Jauharia; Indraswono, Cahyo (LPPM STIE YKPN Yogyakarta, 2023)
This research aims to analyze the perceived usefulness, perceived ease of use, trust, lifestyle, financial literacy and risks in using QRIS as a digital payment tool among students in Yogyakarta. The method used for data collection was a survey using a questionnaire, and obtained 133 respondents by purposive sampling technique. Using multiple linear regression for data analysis, the results showed that perceived usefulness, perceived ease of use, trust, lifestyle, financial literacy and risk influenced the use of QRIS. The research results succeeded in providing support for the proposed TAM theory. Students use QRIS as digital payments when they feel that using QRIS will speed up payments and be flexible to use as a means of payment.